Indigenous media relations: reconfiguring the mainstream - Hiltz, Tia (2014)
Much of the scholarly literature on Indigenous media relations frames Indigenous peoples as passive players in the mainstream media, and focuses on negative elements such as stereotypes. This thesis challenges this view, finding that Indigenous peoples in Canada actively and strategically engage with mainstream and social media as they forward their social and political agendas. This thesis provides an analysis of the counter-colonial narrative in Canada by offering a new perspective on Indigenous media relations, focusing as a case on the Idle No More movement. Emphasizing three dimensions of communication--the mainstream print media, social media, and individuals involved in Indigenous media relations--I examine the ways in which Indigenous agency and empowerment have the potential to change discourses in the media. As sources of insight I draw on a discourse analysis of mainstream news media, a qualitative analysis of social media and on interviews with those who have significant experience in Indigenous media relations. Interviews with prominent media personalities and individuals involved in media relations (including CBC’s Duncan McCue and Janet Rogers; Four Host Nations CEO Tewanee Joseph, and others) illustrate the novel and impactful ways indigenous peoples in Canada are actively and strategically shaping the mainstream media. These representations create a more complex picture of Indigenous peoples as they counter the stereotyped or victimized media narratives within which Indigenous peoples have historically been placed. Graduate 0327 0708 0391 tiahiltz@uvic.ca